Regeneration and multiplication of germplasm resources in seed genebanks: The scientific background - Breese, E.L.; International Board for Plant Genetic Resources (1989)
The regeneration of germplasm resources is an integral part of the conservation programme. This study is directed towards the strategy and tactics of seed regeneration and multiplication by sexual reproduction in relation to problems of maintaining the genetic constitution of the original sampled population.